The Quest for a European Safe Asset—A Comparative Legal Analysis of Sovereign Bond-Backed Securities, E-Bonds, Purple Bonds, and Coronabonds. Issue 2 (13th August 2020) - Grund, Sebastian
Abstract: The European sovereign debt crisis and, more recently, the COVID-19 pandemic have revealed the European Economic and Monetary Union's fragility, which essentially emanates from the inherent tension between a single monetary policy and decentralized fiscal policies. To cushion economic and financial shocks and sever the sovereign-bank doom loop, different proposals to create a common public debt security have been put forward, although none of them has so far seen the light of day. Building on pertinent economic and finance scholarship, this article reviews four promising safe asset proposals from a legal perspective: Sovereign bond-backed securities (SBBS), E-bonds, Purple bonds, and Coronabonds. Rather than focusing on their feasibility under EU law or national constitutional law, this article compares the proposals from an investor perspective against the backdrop of the following formal and functional legal characteristics that render assets 'safe': governing law, dispute settlement forum, investor protection, and investor representation in sovereign debt restructurings. Against this backdrop, targeted recommendations on critical design elements of safe assets, with the aim of reconciling the economic policy objectives with the pertinent legal constraints, are advanced.